Is the marriage of the seven sisters of the south possible? The possibilities of cooperation in Petrol and Gas in Latin America - Hira, Anil (2007)
This article explores the possibility of putting into concrete form the results of a principle initiative of the President Hugo Chávez: the increase of cooperation between the major petroleum companies in Latin America.  In this way, a global view of the petroleum industry is presented, a profile of every one of these Latin American industries and a look at the obstacles and potentials that this initiative presents, and the necessary steps forward to consolidate the petroleum industry.